Pendekatan Komunikatif dalam Pembelajaran Bahasa Arab - Subur Subur (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Language as a tool, not as a goalâ€ becomes the most basic principal of designing communicative approach in the learning of foreign language. In this way, teaching foreign language should make students not only have receptive competence but also demonstrative one. The problem that mostly comes is merely related to how to design and handle such way in the real teaching. This paper just gives an alternative perspective in applying a communicative approach in learning Arabic.